The uses of english as a social practice among Universiti Tunku Abdul Rahman (UTAR) EL students at home - Lee, Sean Shu Hen (2021)
Studies related to social practices at home and how these practices affect the English proficiency levels are limited. There are research gaps that are needed to be filled through further studies. This study aims to determine how social practices in English at home affects the English use and also English proficiency of UTAR EL students. To be exact, the study focuses mainly on social practices in English that improve their interest towards the language, and also to determine the most common social practices amongst UTAR EL students. To conduct the study, the qualitative method, in-depth interviews were conducted with five different participants from UTAR EL. The interviews were transcribed and coded line-by-line to generate different themes that could categorise their statements. Participants also recorded their social practices in English through a recorded journal over a span of three weeks. Findings show that the social practices carried out by all five participants were almost the same, namely social media, listening to music, gaming, and watching television. The study also shows that the participants utilise these social practices indirectly in order to learn the language, and increase their use of it for university subjects. The results show that UTAR EL students improve their English proficiency through the social practices they conduct at home. In general, the study is important for the education sector because it helps students to determine the most effective way of language learning. It also provides teachers with an insight of how different students react to different teaching methods, allowing them to adapt and improve on it.